Single-Cell Transcriptomics-Based Study of Transcriptional Regulatory Features in the Non-Obstructive Azoospermia Testis - Tang, Xiao-juan; Xiao, Qiao-hong; Wang, Xue-lin; He, Yan; Tian, Ya-nan; Xia, Bin-tong; Guo, Yang; Huang, Jiao-long; Duan, Peng; Tan, Yan (Frontiers in Genetics, 2022)
Abstract 18 Non-obstructive azoospermia (NOA) is one of the most important causes of male infertility. Although 19 increased number of congenital factors have been identified, the etiology in the majority of idiopathic 20 NOA (iNOA) cases remains unknown. Herein, using the single-cell RNA-Seq data sets (GSE149512) 21 on the Gene Expression Omnibus (GEO) database, we performed the transcriptional regulatory 22 networks (TRNs) to explain the mutual regulation relationship and the causal relationship between 23 transcription factors (TFs). We defined ten testicular cell types by their marker genes and found that 24 the proportion of Leydig cells (LCs) and macrophages (tMΦ) was significantly increased in iNOA 25 testis. We identified specific TFs included LHX9, KLF8, KLF4, ARID5B and RXRG in iNOA LCs. 26 In addition, we found specific TFs in iNOA tMΦ such as POU2F2, SPIB IRF5, CEBPA, ELK4 and 27 KLF6. All these identified TFs are strongly engaged in cellular fate, function and homeostasis of 28 microenvironment. Possibly, the changes in the activity of above identified TFs affect the function of 29 LCs and tMΦ and ultimately cause spermatogenesis failure. This study illustrate that these TFs play 30 important regulatory roles in the occurrence and development of NOA.